Potensi Kawasan Segara Anakan Sebagai Sarana Fieldwork Pada Pembelajaran Geografi Materi Lingkungan Estuari - Rizal, Syah; Sumarmi, Sumarmi; Bachri, Syamsul; Mutia, Tuti; Ismail, Alice Sabrina (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
Fieldwork learning is a form of implementing real geography learning to improve students' competence in understanding geosphere phenomena. The various benefits of fieldwork learning require the right tools in its application. The Segara Anakan area with all its appearances and resources has the potential to be used as a means of learning important fieldwork on estuarine environmental material. This study aims to explore the potential and strategy of the Segara Anakan Area as a means of learning geography fieldwork on estuarine environmental material. This research is included in the qualitative descriptive research. The data used are primary data from field observations and secondary data from scientific literature. The analysis used is descriptive analysis to describe the potential of the Segara Anakan Area as a means of learning fieldwork in an estuary environment. The results showed that the Segara Anakan area has objects that can be used as objects of study according to competence and indicators of estuarine environmental material. This fieldwork strategy is carried out by determining the object of study, accessibility, instruments, equipment, and materials to be used during field activities. During the activity, students make observations, collect data, and listen to the teacher explain the object of study. The implementation of fieldwork in the Segara Anakan area has constraints such as time, costs, permits, and threats when carrying out fieldwork.